Guazuma ulmifolia (Sterculiaceae), a new natural host of 16SrXV phytoplasma in Costa Rica - Villalobos Muller, William (2011)
Guacimo trees (Guazuma ulmifolia, Sterculiaceae) showing witches’ broom symptoms (GWB), small leaves, short internodes, stunting and no flower and fruit production were observed on side roads and fences in different areas of Costa Rica. The occurrence of phytoplasma infection in GWB trees was evaluated by transmission electron microscopy (TEM), and by molecular analyses based on 16SrDNA: nested-PCR/RFLP, sequencing and phylogenetics. Phytoplasmas were observed only in the sieve cells of symptomatic trees by TEM. The infection was confirmed by nested-PCR; amplicons of about 1.2 kb were obtained from all DNA samples from symptomatic trees. The RFLP analysis generated patterns identical among GWB samples and showed a relationship of this phytoplasma to hibiscus witches’ broom group (16SrXV). The 16S rDNA sequence (1460 nt), obtained from the P1A/16S-SR semi-nested-PCR products of two phytoplasma strains, shared 98.8% similarity with ‘Candidatus Phytoplasma brasiliense’ (GenBank accession: AF147708). The virtual RFLP pattern indicated a similarity coefficient of 0.95 with 16Sr group XV-A (AF147708), suggesting that the GWB phytoplasma may represent a new subgroup within this group. This is the first report of a phytoplasma infecting the neotropical tree species G. ulmifolia and the natural occurrence of a phytoplasma strain closely related to ‘Ca. Phytoplasma brasiliense’ in Costa Rica.